The good fight : a novel - Steel, Danielle (New York : Random House Large Print Publishing, 2018)
"The daughter and granddaughter of prominent Manhattan lawyers, Meredith McKenzie spent her childhood in Germany as her father prosecuted Nazi war criminals at the Nuremberg trials. When her family returnd to the United States, she blazed her own trail, determined to become a lawyer despite her traditional, conservative father$1 (Bs objections. s
Keywords: Families -- Fiction; Nineteen sixties -- Fiction; United States -- History -- 20th century -- Fiction; Large type books